2019
DOI: 10.1007/s11947-019-02251-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Zygosaccharomyces rouxii Population in Concentrated Grape Juices by Thermal Pasteurization and Hydrostatic High Pressure Processing

Abstract: Zygosaccharomyces rouxii is the most frequent spoilage yeast species detected in concentrated grape juice. In order to reduce Z. rouxii populations and consequently extend the microbiological shelf life of this product, different programs of thermal pasteurization and high hydrostatic pressures processing were evaluated. Results showed that pasteurization temperatures higher than 75 °C are necessary to reduce Z. rouxii population in concentrated grape juice. Reduction of 7 logarithms can be reached after 90 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…Several authors have previously reported that HHP applied at commercial conditions (> 400 MPa, > 3 min) does not affect the total phenolic content in fruits such as strawberry and blackberry (Patras et al 2009a, b), mango (Elizondo-Montemayor et al 2020), tomato and carrot (Patras et al 2009a, b). However, most previous studies evaluating the effect of HHP on phenolics content have been performed in fruit and vegetables processed into pulp or juice prior to HHP treatment with the focus of microbial stabilization (Klug et al 2018;Rojo et al 2019) and enzyme inactivation (Moralesde la Peña et al 2018), and thus there is scarce information on the effect of HHP applied at physiological conditions (come-up time, and pressures below 150 MPa) in whole fresh produce to determine its potential use as an abiotic elicitor of phenolic compounds. Likewise, most previous reports are Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have previously reported that HHP applied at commercial conditions (> 400 MPa, > 3 min) does not affect the total phenolic content in fruits such as strawberry and blackberry (Patras et al 2009a, b), mango (Elizondo-Montemayor et al 2020), tomato and carrot (Patras et al 2009a, b). However, most previous studies evaluating the effect of HHP on phenolics content have been performed in fruit and vegetables processed into pulp or juice prior to HHP treatment with the focus of microbial stabilization (Klug et al 2018;Rojo et al 2019) and enzyme inactivation (Moralesde la Peña et al 2018), and thus there is scarce information on the effect of HHP applied at physiological conditions (come-up time, and pressures below 150 MPa) in whole fresh produce to determine its potential use as an abiotic elicitor of phenolic compounds. Likewise, most previous reports are Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The single treatment volume of the juice was 50 mL, and each treatment was used in at least 3 parallel experiments. For CTS treatment, the grape juice samples were sterilized at 85 °C for 10 min [ 26 ]. The ultrasound-related treatments were based on the method by Liao et al [ 11 ] with minor changes.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the primary new non-thermal technologies that are on the rise are high hydrostatic pressure (HHP), pulsed electric fields (PEF), ultrasound (US), ultraviolet light (UV), and cold plasma, among others [33]. In this sense, HHP has achieved the greatest success [34], with a continuously expanding market due to its capacity to reduce the microbial load of both pathogens and disruptive microorganisms in multiple juice matrices, consequently resulting in an extension of the storage period [35] while preserving the organoleptic, nutritional, and phytochemical characteristics of the juices [36,37]. Due to the intrinsic characteristic of this technology, at moderate temperatures, high pressures do not affect the covalent bonds during the pressurization process [38,39], with food biomolecules minimally affected in vegetable-and fruit-based drinks [40,41].…”
Section: Introductionmentioning
confidence: 99%